Metabolism of ‘Syrah’ grapevine in the Brazilian semiarid northeast under three irrigation strategies - Caio Márcio Guimarães Santos; Márcia Moura Moreira; João Domingos Rodrigues (Semina: Ciências Agrárias, 2013)
The almost complete absence or misdistribution of water as a natural resource frequently constitute a limiting factor for plant growth and development in the semi-arid northeastern Brazil. In this context, the use of appropriate irrigation techniques is an essential and indispensable factor for proper functioning of the primary and secondary metabolisms in plants. This study aimed to assess the metabolism of the Syrah grapevine in the semi-arid northeastern Brazil, by using three irrigation strategies (controlled deficit irrigation [CDI], deficit irrigation [DI], and full irrigation [FI]). The research was conducted at Embrapa Semiarid (Embrapa-Brazilian Agricultural Research Corporation), Experimental Field of Bebedouro, municipality of Petrolina, state of Pernambuco, Brazil. The statistical design was randomized blocks, with a 3 × 6 factorial scheme. Six samplings were performed throughout the experiment cycle at 54, 60, 73, 87, 101, and 115 days after pruning (DAP). We analyzed the total soluble sugars, reducing sugars, total soluble protein, and invertase activity. Analysis of variance and the F test were performed for all analyzed variables. The means were compared using the Tukey test at 5% significance. At the end of the experiment cycle, DI was found to increase the average acid invertase activity in the plant cell wall. Further, by the end of the experiment cycle, the total soluble sugars and reducing sugars increased in all plants in the three irrigation strategies. Thus, we conclude that it is possible to reduce water consumption in vineyards of the semi-arid northeastern Brazil, without significantly affecting the protein and sugar metabolisms in the plants.